USE OF COMICS IN ENHANCING SPEAKING INTERACTION SKILLS OF PROSPECTIVE ENGINEERS IN ESP CLASSROOM (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article is devoted to the problem of teaching English for specific purposes (ESP) of engineering students. The research reports on the effectiveness of using comics as an innovative tool for enhancing English speaking interaction of engineering students in ESP classroom. Particular attention is paid to the use of online platforms for creating comics, as a means of improving professional English speaking skills in the context of engineering activities. It is noted that online resources for creating comics are accessible and easy to use, which makes it possible to integrate this method into the educational process. The advantages and disadvantages of using comics as a tool for enhancing speaking skills in the educational process are revealed. It is defined that comics allow the students to work with technical terms and the realities of professional communication by creating context based on engineering situations. Due to the visual component of comics, the students can more effectively understand the context of communication and build their speech strategies according to real-life situations. The study defines that using comics may require more preparation time and is not always suitable for every topic or type of learning activity. The research shows that although comics have a certain template, the tasks based on comics while learning English allow developing coherent foreign language speech, enriching students’ vocabulary, analyzing the material read and identifying the main points. The use of comics enables engineering students not only to work actively with the text but also to develop their creative abilities by creating their own comics using modern Internet resources and mobile technologies. The findings suggest that working with comics not only increases the motivation of engineering students, but also provides interactive and dynamic learning that improves their English language skills.